ELEMENTARY SCHOOL BUILDINGS CONDITION ASSESSMENT: CASE OF PRIMORJE-GORSKI KOTAR COUNTY (CROATIA) (Advances in Civil and Architectural Engineering, 2023)
This study deals with the condition examination of elementary school buildings in Primorje-Gorski Kotar County, Croatia. For schools to be functional and of high quality, adequate maintenance is mandatory. Therefore, school maintenance programs need information on the building's condition based on systematic and comprehensive assessments as a primary input. This study aims to establish a framework for assessing the condition of school buildings, based on which information can be obtained quickly and practically regarding the condition of all critical facility elements. To this end, a database on schools and their conditions was created. The conditions of school buildings in terms of damage and defects and their causes were determined. Descriptive and inferential statistical operations were performed on the collected data. A condition assessment of the buildings was performed using a questionnaire survey among the principals, based on the school buildings division model developed in this study; the model presents building elements and a systematic visual condition rating scale. According to the available data, this is Croatia's first condition assessment on elementary school buildings. The main results show that on average, the examined schools are in good condition. Moreover, according to the results, the school building condition is most affected by dilapidation and lack of financial resources.